Quantitative risk assessment and eco-engineering mitigation strategies for debris flows utilizing dynamic process simulation in Shuzheng gully, Jiuzhaigou valley scenic and historic interest area - Yang, Dongxu; Zong, Xin; Wu, Bin; Wang, Yiming; Liang, Binqi; Wan, Fangkai; Liu, Jiankang; Peng, Jiansong (Frontiers in Earth Science, 2025)
Debris flows pose severe threats to ecologically sensitive mountain areas, especially UNESCO World Heritage sites, where traditional mitigation measures often fail to balance risk reduction with environmental conservation. This study develops an integrated framework that combines high-resolution dynamic simulation with adaptive eco-engineering strategies. Using the Massflow model calibrated with empirical hydrodynamic parameters and 1m-resolution DEM data, we simulated debris flow scenarios under 20- and 50-year rainfall return periods. Under the 50-year event, debris flows reached peak velocities of 6.49 m/s and discharges of 38.33 m³/s. Hazard zoning revealed that high-, medium-, and low-risk zones accounted for 1.16%, 8.07%, and 90.77% of the study area, respectively, threatening 11,745.33 m² of infrastructure in Shuzheng Village. To mitigate these risks while preserving the natural landscape, we designed a novel pine pile–gabion composite dam (PPGD) system integrated with terrain-adaptive ecological restoration. The PPGD raises the erosion base level to dissipate impact energy and features a stepped gabion structure that promotes progressive solid-liquid separation, thereby reducing sediment concentration and enhancing ecological resilience. Simulation results show that three cascaded PPGDs reduced the total inundation extent by 45.78%. At the same time, peak flow velocities downstream of Dams No. 1, No. 2, and No. 3 were decreased by 45.34%, 40.34%, and 37.14%, respectively, compared to upstream values. These findings highlight the effectiveness of coupling dynamic process modeling with eco-engineering interventions for quantitative debris flow risk governance and sustainable landscape protection in ecologically sensitive mountain areas.